2012
DOI: 10.1115/1.4007350
|View full text |Cite
|
Sign up to set email alerts
|

On the Steady Performance of Annular Hydrostatic Thrust Bearing: Rabinowitsch Fluid Model

Abstract: The present theoretical analysis investigates the simultaneous effect of lubricant inertia and non-Newtonian pseudoplastic lubricant (lubricant blended with viscosity index improver and viscosity thickener)–Rabinowitsch fluid model on the performance of externally pressurized annular hydrostatic thrust bearings. A close form solution is obtained for pressure distribution. The effect of centrifugal inertia on the pressure distribution in the recess region is considered by taking non-constant recess pressure und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…This model has its significance as the three major categories for fluid are depicted for different values of nonlinear factor β, i.e., for β = 0 this model represents Newtonian fluids, for β < 0 it represents shear thickening fluids, and for β > 0 it exhibits behaviour of shear thinning fluids. Many researchers had considered this model for the experimental and theoretical analysis of squeeze film, annular disk, externally pressurized bearing, journal bearing, and pivoted curved slider bearings [8,9]. However, no one has attempted to examine Rabinowitsch fluid model for peristaltic flows in a curved channel.…”
Section: Introductionmentioning
confidence: 98%
“…This model has its significance as the three major categories for fluid are depicted for different values of nonlinear factor β, i.e., for β = 0 this model represents Newtonian fluids, for β < 0 it represents shear thickening fluids, and for β > 0 it exhibits behaviour of shear thinning fluids. Many researchers had considered this model for the experimental and theoretical analysis of squeeze film, annular disk, externally pressurized bearing, journal bearing, and pivoted curved slider bearings [8,9]. However, no one has attempted to examine Rabinowitsch fluid model for peristaltic flows in a curved channel.…”
Section: Introductionmentioning
confidence: 98%
“…Singh at el. adopted Rabinowitsch fluid model for theoretical investigation of performance properties of many film lubricated bearings in different lubrication regimes [8][9][10][11]. To study the characteristics of bearings lubricated with non-Newtonian lubricants, Rabinowitsch fluid model is one of the best and experimentally verified fluid models [12].…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the externally pressurized bearings, circular hydrostatic thrust bearings are of great importance for industrial and engineering applications due to its wide uses in high speed rotating machines. Researchers have also paid significant attention towards improvement of performance of these bearings under various operating and lubricating conditions [1][2][3][4][5]. Several investigations have been carried out to analyse the dependence of different performance properties of these bearings on rotational inertia, fluid compressibility and temperature variation of the fluid [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…To study the lubrication regimes with such lubricants, many non-Newtonian models such as couple stress, power law, micropolar and Casson models are of common interest. Amongst these models, cubic stress (Rabinowitsch) fluid model [1][2][3] is an established model to analyze the non-Newtonian behavior of the fluid. Wada and Hayashi [26] showed that the lubricants blended with viscosity index improver behave like pseudoplastic fluids, which can be analyzed with cubic stress (Rabinowitsch) fluid model given by following relation for one-dimensional fluid flow:…”
Section: Introductionmentioning
confidence: 99%